Pre- and Postoperative Urea Levels in Open Heart Surgery: Assessment as a Risk Factor for Predicting Mortality - A Retrospective Analysis - Toprak, Burak; Kanat Toprak, Çise; Cihan, Hasan (Scientific Reports in Medicine, 2025)
Background: Open-heart surgery, while essential for managing severe cardiovascular diseases, carries a high risk of postoperative complications, particularly acute kidney injury (AKI), associated with elevated urea levels. High urea reflects renal impairment and inflammatory stress, both of which impact patient survival, highlighting the need for reliable biomarkers to predict mortality and optimize perioperative care. Aims: This study evaluated the predictive value of preoperative and postoperative urea levels in estimating mortality risk in open-heart surgery patients. Despite the established clinical importance of urea, its potential as a prognostic tool remains underutilized. Methods: We conducted a retrospective analysis of patient data, focusing on the relationship between urea levels and mortality outcomes in individuals who had undergone open-heart surgery. Multivariate analyses were performed to assess the independent impact of urea levels on mortality risk. Results: Findings showed that each unit increase in postoperative urea was linked to a 5% increase in mortality risk, underscoring its value as a prognostic indicator. Higher preoperative urea levels also correlated with decreased survival, particularly among high-risk patients. Conclusions: Both preoperative and postoperative urea levels are critical indicators of mortality risk following open-heart surgery. Routine monitoring of these biomarkers could improve postoperative outcomes, especially for high-risk groups. This study supports incorporating urea levels into standard perioperative assessments to enhance patient survival rates.